A qualitative study on factors of management institute: alumni association contributing to the institute’s growth - Sandhane, Raghav; Patil, Kanchan (Institute of Advanced Engineering and Science, 2025)
Institutes imparting management education in India are rising in numbers. They are struggling to keep in pace with the competition and are facing several challenges. After studying these challenges, researchers have proposed several approaches including better advertisement, having experienced faculty and attracting companies for recruitment as possible areas for improvements. One of the proposed areas that seems to address a variety of the challenges, is having a better institute-alumni association. The research conducted on the alumni-institute association thus far have highlighted only a limited number of areas. Hence, this grounded study was conducted to bring forth all the possible factors and the sub factors of association between the alumni and the institute. This is a qualitative study that uses dialogic theory as an underpinning theory to aid data collection and analysis. The 13 decision makers with minimum of 15 years of teaching/administration experience in post graduate institutes were interviewed. The empirical data was analyzed using code analysis technique. The analysis presented a model of factors and sub factors to enable better institute-alumni association. The model clearly identifies the areas to focus on for developing a strong alumni association. One of the foremost findings of the research is the identification of the need for institute’s contribution in alumni growth and the ways to make this happen. Institute risk identification is another important area for alumni contribution. The developed model serves as a ready reckoner for the management institutes in its pursuit of growth.